The Effect of Work Environment and Work Motivation on Employees Performance Cileungsi Office - Novingky Ferdinand; Ermi Herawati (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
This study used a questionnaire as the research instrument and the sampling technique in this study used a saturated sampling technique with 32 respondents. Data was collected using multiple linear regression analysis with hypothesis testing. From the results of the study, it is known that the Work Environment and Work Motivation contribute 44.3% to the increase in Employee Performance while the remaining 55.7% is contributed by variables other than Work Environment and Work Motivation. The test results show that partially the work environment has a positive and significant effect on employee performance, partially Work Motivation has a positive and significant effect on employee performance, and simultaneously work environment and Work Motivation have a positive and significant effect on employee performance